An Effective Fabrication of Sheet-Like Iron by Electrochemical Deposition - Tao, Fei-Fei; Wu, Qiu-Xia; Wang, Lin-Xia (Asian Journal of Chemistry, 2011)
The metal iron sheets were successfully fabricated with the help of cetyltrimethylammonium bromide (CTAB) combined with the electrochemical deposition technology. The sheet-like structures perpendicularly grew up on the foil and formed the array constructed by iron sheets. To the best of our knowledge, it is the first report on sheet-like iron. This method is very facile and effective to prepare the sheet-like structure with the uniform thickness. Especially, the addition of CTAB can not only effectively attribute to the formation of the sheet-like structure as shapecontroller, but also prevent iron from oxidizing as the protective agent. The effects of the experimental parameters on the morphologies of the products were deeply discussed by scanning electron microscopy and the possible formation mechanism was proposed. And the size of iron sheets and the sheet intensity in the array can be controlled by adjusting the concentration of CTAB and the electric potential, respectively.